Distance spectrum and distance (signless) Laplacian spectrum of some subdivision graphs - Lu, Pengli; Liu, Wenzhi (Utilitas Mathematica, 2020)
Let G be a connected graph with distance matrix ~D(G), distance Laplacian matrix C{G) and distance signless Laplacian matrix Q(G). The T>—eigenvalues, C—eigenvalues and Й—eigenvalues are the V—spectrum, £—spectrum and fi—spectrum, respectively. In this paper, we give a complete description of the Pspectrum, C—spectrum and Qspectrum of Gi®Ga, Gì VG2 and G1VG2, when Gi and Gì are regular graphs. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.